Evaluating and Criticizing some Translations of Part 30 of Holy Quran from the Literal, Rhetoric and Syntactic Viewpoints. [In Persian] - Sadeq Fat’hiDehkordi (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2018)
This paper evaluates and criticizes some translations of part 30 of holy Quran from the literal, rhetoric and syntactic viewpoints. In this regard, mistakes of respectful translators in some cases such as failure to observe limit, inattention to emphasis, inattention to antecedence and precedence in verses, negligence of morphological and syntactical points, failure to apply exact equivalences of the words, prevention from Persian writing and application of Arabic words have been evaluated based on different interpretations and also rhetoric and lexical books and finally the proposed translation has been presented. This article tries to critique the translation transcripts of the honorable professors Abolqasem Payandeh, Mohammad Mahdi Fouladvand, Seyyed Ali Mousavi Garmaroodi and Seyyed Jalaloddin Mojtabavi from part 30 of the holy Quran using a descriptive-analytical method, and in addition to stating  rhetorical,syntactic and lexical problems present in these transcripts, propose a suggested  translation so as to increase the richness of  Quranic translation.